Island of the lost : shipwrecked at the edge of the world - Druett, Joan. (Chapel Hill, N.C. : Algonquin Books of Chapel Hill, 2007)
"Auckland Island is a godforsaken place in the middle of the Southern Ocean, 285 miles south of New Zealand. With year-round freezing rain and howling winds, it is one of the most forbidding places in the world. To be shipwrecked there means almost certain death." "In 1864 Captain Thomas Musgrave and his crew of four aboard the schooner Grafton wreck on the southern end of the island. Utterly alone in a dense coastal forest, plagued by stinging blowflies and relentless rain, Captain Musgrave - rather than succumb to this dismal fate - inspires his men to take action. With barely more than their bare hands, they build a cabin and, remarkably, a forge, where they manufacture their tools. Under Musgrave's leadership, they band together and remain civilized through even the darkest and most terrifying days." "Incredibly, at the same time on the opposite end of the island - twenty miles of impassable cliffs and chasms away - the Invercauld wrecks during a horrible storm. Nineteen men stagger ashore. Unlike Captain Musgrave, the captain of the Invercauld falls apart given the same dismal circumstances. His men fight and split up; some die of starvation, others turn to cannibalism. Only three survive. Musgrave and all of his men not only endure for nearly two years, they also plan their own astonishing escape, setting off on one of the most courageous sea voyages in history." "Using the survivors' journals and historical records, maritime historian Joan Druett brings this untold story to life."--BOOK JACKET.
Machine derived contents note: Contents -- One A Sturdy Vessel 000 -- Two Open Sea 000 -- Three The Islands 000 -- Four Wrecked 000 -- Five Shelter 000 -- Six Prey 000 -- Seven The Cabin 000 -- Eight Democracy 000 -- Nine Routine 000 -- Ten Dire Necessity 000 -- Eleven The Jaws of Hell 000 -- Twelve Privation 000 -- Thirteen The Hunt 000 -- Fourteen Equinox 000 -- Fifteen Summer 000 -- Sixteen Raynal's Forge 000 -- Seventeen Boats 000 -- Eighteen Escape 000 -- Nineteen Deliverance 000 -- Twenty A Sentiment of Humanity 000 -- Twenty-one Rescue 000 -- Twenty-two Reunion 000 -- Twenty-three Answers 000 -- Aftermath 000 -- Author's Note 000.
New Zealand author.
Includes bibliographical references.
Keywords: Grafton (Schooner); Invercauld (Ship); Shipwrecks -- New Zealand -- Auckland Islands; Shipwreck survival -- New Zealand -- Auckland Islands; Auckland Islands (N.Z.) -- Description and travel